Behavioral Activation (BA) in the Management of Depression in an Adolescent with Down Syndrome in Dubai - Sidra Shadan; Sarah Almarzooqi; Meshal A. Sultan (Case Reports in Psychiatry)
Depression has been commonly treated with psychotherapy and/or pharmacotherapy for several decades. Ongoing research in the field has suggested promise for behavioral activation (BA), a form of psychotherapeutic intervention, as a means of increasing engagement in adaptive activities and developing skills to counter avoidance in individuals suffering from depression. In this case report, we present the treatment course of BA for an adolescent with Down syndrome (DS), presenting with depression. A multidisciplinary approach was utilized in developing a personalized management plan for the patient since the initial presentation. Sessions at the outpatient psychiatry clinic alternated between in-person visits and virtual ones, due to circumstances associated with physical distancing with the COVID-19 pandemic. Parents were included as integral parts of the management plan, and education, strategic implementation of BA, and barriers to care were discussed extensively to support the adolescent through the course of her treatment. Within 6 weeks of introducing BA, positive outcomes were noted in the patient, with the resolution of her clinical depression. In this report, we discuss BA further as a potentially effective therapeutic approach to the treatment of depressive symptoms in children and adolescents with DS and intellectual disabilities.